Microwave Assisted Catalytic Activity of Some bis-5(6)-Nitrobenzimidazole Salts for Heck and Suzuki Cross-Coupling Reactions - Sireci, Nihat; Yilmaz, Ulku; Kucukbay, Hasan (Asian Journal of Chemistry, 2010)
A mixture of bis-5(6)-nitrobenzimidazole salts (2a-h), Pd(OAc)2 and K2CO3 in DMF-H2O catalyzes, in good yield the Suzuki and Heck cross-coupling reactions for synthesis of biaryl and stilbene derivatives assisted by microwave irradiation in the short time.